(untitled) (Tanzania Medical Journal, 2015)
Background: There is paucity of data describing magnitude of anaemia among HIV infected children in Tanzania. Most of the studies among anaemic Tanzanian children were conducted before the era of HIV and HAART.Materials and Methods: This was a cross sectional study aimed at determining the prevalence and morphological types of anaemia among HIV-infected children attending public hospitals in Dar es Salaam. The prevalence of anaemia was determined as a percentage among all children infected with HIV. To describe the spectrum of red blood cell (RBC) morphology on blood films a pairwise comparison was conducted using Chi squire test or Fisher’s exact test.Findings: In this study the overall prevalence of anaemia (Hb<11g/dl) among 167 HIV infected children attending public hospitals was 44%. Among enrolled children, 35 (21.1%) had mild anaemia, 14(8.4%) had moderate anaemia and 26(15.6%) had severe anaemia. Microcytic anaemia was found to be the commonest (73%) type of anaemia followed by normocytic normochromic anaemia. The abnormal red blood cell shape (P=0.02), microcytosis (P<0.001), hypochromia (P<0.001), and abnormal platelet morphology (P<0.001), were common in anaemic HIV infected children compared to those who had no anaemiaConclusions and recommendations: The finding suggests that anaemia is common among HIV children even in the era of HAART. Microcytic hypochromic anaemia was the commonest type of anaemia suggesting the role of iron deficiency or anaemia of chronic infection. Further studies on the aetiology of anaemia in HIV infected children are needed